Hybrid technologies for power generation - Lo Faro, Massimiliano; Barbera, Orazio; Giacoppo, Giosue (Academic Press, 2021)
Hybrid Technologies for Power Generation addresses the topics related to hybrid technologies by coupling conventional thermal engines with novel technologies, including fuel cells, batteries, thermal storage and electrolysis, and reporting on the most recent advances concerning transport and stationary applications. Potential operating schemes of hybrid power generation systems are covered, highlighting possible combinations of technology and guideline selection according to the energy demands of end-users. Going beyond state-of-the-art technological developments for processes, devices and systems, this book discusses the environmental impact and existing hurdles of moving from a single device to new approaches for efficient energy generation, transfer, conversion, high-density storage and consumption. By describing the practical viability of novel devices coupled to conventional thermal devices, this book has a decisive impact in energy system research, supporting those in the energy research and engineering communities.